MR-SimExCoverage: Multi-robot Simultaneous Exploration and Coverage. (July 2020) - Nair, Vishnu G; Guruprasad, K.R.
Highlights: Combines exploration, mapping and coverage. Best utilization of onboard sensors such as long range distance sensors. Combines the advantages of offline and online coverage path planning. Graphical abstract: Abstract: In this paper, we present a novel problem of simultaneous exploration and area coverage by multiple cooperating mobile robots. As the robots cover an initially unknown region, they perform intermittent exploration of the region and build a map, which in turn is used to plan the coverage path. We use a Voronoi partition based multi-robot coverage strategy using the Manhattan distance metric to solve the coverage problem and a frontier based exploration strategy for exploration mapping. We provide results of simulation using Matlab/V-rep environments to demonstrate the proposed multi-robot simultaneous exploration and coverage (MR-SimExCoverage) problem using the spanning tree based coverage (STC) algorithm.